THE USE OF PQ4R IN TEACHING STUDENTS' READING COMPREHENSION OF NARRATIVE TEXT - Bayu , Muhamad (2013)
The research entitled "The Use of PQ4R in Teaching Students' Reading Comprehension of Narrative Text" was aimed at answering the question whether or not the use of PQ4R strategy significantly improved students' reading comprehension ability and the students' responses toward PQ4R strategy. This quasi-experimental research was conducted at the first grader at one public senior high school in Cianjur. In addition, questionnaire and interview were employed to reveal the students' responses. Two classes were assigned as experimental and control groups and each class consisted of 38 students. The data were collected through pre-test, post-test, questionnaire, and interview. Quantitative method was used to analyze the data by comparing the mean scores of both groups in pre-test and post-test. Furthermore, the data taken from questionnaire and interview were also analyzed to find out students' responses toward PQ4R strategy. The result shows that PQ4R strategy highly improved students' reading comprehension of narrative text (tobt > tcrit or 2.654 > 2.000) and the data from questionnaire and interview showed that students gave positive responses toward PQ4R strategy. Moreover, further research is suggested to examine whether or not PQ4R strategy is applicable in other degrees. Penelitian yang berjudul "The Use of PQ4R in Teaching Students' Reading Comprehension of Narrative Text" bertujuan untuk menjawab perumusan masalah apakah penggunaan strategi PQ4R dapat secara signifikan meningkatkan kemampuan pemahaman membaca siswa dan respon siswa terhadap strategi PQ4R. Penelitian quasi-experimental ini dilaksanakan terhadap salahsatu kelas X SMA di Cianjur. Sebagai tambahan, kuesioner dan wawancara dilaksanakan untuk mengetahui respon siswa. Dua kelas digunakan sebagai kelas eksperimental dan kelas control dan setiap kelas terdiri dari 38 siswa. Data dikumpulkan melalui pre-test, post-test, kuesioner dan wawancara. Penelitian ini menggunakan metode kuantitatif dengan membandingkan rata-rata yang diperoleh oleh kedua kelas dalam pre-test dan post-test. Selanjutnya, informasi yang diperoleh dari kuesioner dan interview dianalisa untuk mengetahui respon siswa terhadap strategi PQ4R. Berdasarkan hasil dari penelitian dapat dilihat bahwa strategi PQ4R secara sangat signifikan mampu meningkatkan kemampuan siswa dalam pemahaman membaca teks narratif. (tobt > tcrit atau 2.654 > 2.000) dan informasi dari kuesioner dan wawancara menunjukan bahwa siswa memberikan respon positif terhadap strategi PQ4R. Penelitian selanjutnya diharapkan untuk menguji apakah strategi PQ4R dapat diterapkan di tingkat sekolah yang lain.